Penggunaan Vidio Pembelajaran Berbasis Canva Untuk Meningkatkan Hasil Belajar Siswa Pada Materi Dinamika Litosfer Di SMA Negeri I Suwawa Timur - Dudetu, Candrawaty; Rusiyah, Rusiyah; Pambudi, Moch. Rio (-, 2025)
Problems related to learning outcomes are common challenges that are often experienced by many students throughout the educational process of students. Some of the main causes of this problem include low understanding of concepts, weak learning motivation, use of inappropriate learning strategies, ineffective time management, and pressure or stress. This study aims to examine the effectiveness of using Canva-based learning videos in improving the learning outcomes of class X-A students on the material of lithosphere dynamics at SMA Negeri 1 Suwawa Timur. The method used in this study is Classroom Action Research (CAR). Through the application of the Project Based Learning (PjBL) learning model combined with Canva-based interactive video media, two learning cycles were carried out to measure the development of student learning outcomes. The results of the data analysis showed that in cycle I, the average student achievement score was 73.07% which was included in the good category. After corrective actions were taken in cycle II, there was a significant increase with an average score reaching 83.23%, which was included in the very good or optimal category. These findings indicate that the use of Canva-based video media has been proven to be able to provide a positive contribution to improving students' understanding of concepts and learning outcomes in geography material, especially lithosphere dynamics.